Flutter analysis for bridge decks using Lattice Boltzmann Method (Engineering Review, 2015)
Aiming at using the Lattice Boltzmann Method for flutter analysis of the bridge decks, a fluid- structure interaction algorithm is developed  within the framework of multiple –relaxation- time Lattice Boltzmann  Method. In the present algorithm, the unsteady fluid dynamics  is computed by the extended two-dimensional Lattice Boltzmann Method by incorporating the dynamic Smagorinsky subgrid scale  model, while the structure is modelled by an elastically suspended rigid body and its dynamic analysis is performed by using a Runge–Kutta method. A staggered coupling strategy is adopted to couple the fluid solver and the structure solver. To demonstrate the applicability of the presented algorithm, flutter analyses of the Second Forth Road Bridge and the Guamá River Bridge are employed. The numerical results are compared with wind tunnel measurements. It is shown that the  presented algorithm has a good prediction for the flutter onset  velocities of the Forth Road Bridge and the Guamá River Bridge and thus indicates, to a certain extent, the applicability of the presented algorithm.